2020
DOI: 10.1002/cncr.32693
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer screening disparities between women with and without disabilities: A national database study in South Korea

Abstract: Background Health disparities among individuals with disabilities remain underrecognized. The objective of the current study was to investigate: 1) whether disparities exist in breast cancer screening rates among women with disabilities compared with women without disabilities; 2) whether breast cancer screening rates vary according to the type and severity of disabilities; and 3) trends in breast cancer screening disparities according to disability status over time. Methods Using national administrative datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…21 Other literature suggests that people with ID also participate poorly in screening programs, and this lowers their chances for early detection of cancer types targeted by screening. 20,[39][40][41] For all cancer types in the Dutch screening program (colon, cervical, and female breast), this study showed elevated mortality for people with ID in comparison with the general population. This underlines international concerns about access to and participation in population screening and shows the need to investigate this further.…”
Section: Discussionmentioning
confidence: 67%
“…21 Other literature suggests that people with ID also participate poorly in screening programs, and this lowers their chances for early detection of cancer types targeted by screening. 20,[39][40][41] For all cancer types in the Dutch screening program (colon, cervical, and female breast), this study showed elevated mortality for people with ID in comparison with the general population. This underlines international concerns about access to and participation in population screening and shows the need to investigate this further.…”
Section: Discussionmentioning
confidence: 67%
“…Breast Cancer Screening: Breast cancer is the most frequently diagnosed cancer and the second most common cause of cancer-related death in women. However, with the possibility of early detection through routine screening, the mortality has decreased by 20% with an improved 5-year survival rate ( 32 ). The U.S Preventive Services Task Force (USPSTF) guideline recommends “biennial screening mammography for all women aged 50 to 74 years” including IDW ( 33 ).…”
Section: Resultsmentioning
confidence: 99%
“…Significant disparities were also found in breast cancer screening, especially in women with severe and mental disabilities. 20 Significant disparities were reported in gastric cancer screening in Korea, especially among people with severe disabilities, renal failure, or mental disabilities. 21 Fujiwara et al 22 reported low rates of cancer screening in schizophrenic patients.…”
Section: Introductionmentioning
confidence: 99%